(untitled) (Research, Society and Development, 2021)
Northeast Brazil is characterized as an important region for melon production worldwide. Currently, the states of Brazil Ceará (CE) and Rio Grande do Norte (RN) are attributed the production of around 90% of the melon produced in the country, both for export and for domestic consumption, which opens a range of opportunities for the use of discarded melon as the main raw material in alternative food products and ventures. The following research proposes the elaboration and characterization of melon molasses from discarded melon of three different varieties produced in Rio Grande do Norte, Pele de sapo, Cucumis melo ’Santa Claus’, Yellow Cucumis melo L. (Inodorus Group)’ Canary ’and green, Cucumis melo L. (Inodorus Group)’ Honey Dew ’. The physical-chemical analyzes were carried out in the food technology laboratory of the Semi-arid Rural Federal University. These analyzes were: Soluble solids, SS (oBrix), pH, Titratable acidity, (ATT) (%, citric acid), Electrical conductivity, (mS / cm), Total sugars (%, g / 100g), Total phenols (EAG, mg / 100g) EAG = Gallic acid equivalent, Antioxidant activity (IC50, mg / mL). This research promotes and contributes to achieving the sustainable development goals (SDG) proposed by the UN in its 2030 agenda, specifically goal No. 12, "Responsible consumption and production".